1990
DOI: 10.1128/jb.172.5.2360-2366.1990
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of glucoamylase from the yeast Schwanniomyces castellii

Abstract: Expression of the 146-kilodalton (kDa) extracellular glucoamylase by the budding yeast Schwanniomyces castellii is induced by maltose and starch. By use of antiglucoamylase antisera, we found that this expression was regulated at the level of the mRNA, taking place within 30 min after exposure of yeast cells to the respective sugars. Polyacrylamide gel electrophoresis analysis of the in vitro-translated products of total RNA from maltose-treated cells established that the glucoamylase precursor was approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…Several of its amylolytic enzymes have been characterized, including amylases and glucoamylase (1,9), as well as an invertase (17). In addition, we also characterized an extracellular ␤-fructofuranosidase (Ffase) from this yeast that hydrolyzes sucrose, 1-kestose, and nystose (5).…”
mentioning
confidence: 99%
“…Several of its amylolytic enzymes have been characterized, including amylases and glucoamylase (1,9), as well as an invertase (17). In addition, we also characterized an extracellular ␤-fructofuranosidase (Ffase) from this yeast that hydrolyzes sucrose, 1-kestose, and nystose (5).…”
mentioning
confidence: 99%
“…Northern analysis revealed that maltase mRNA was induced twice as much in maltoseversus sucrose-grown cells (Fig. 4) (25), Schwanniomyces castellii (8,9), Candida tsukubaensis (18,19), and Candida tropicalis (32). Little information regarding the substrate specificity and regulation of the C. albicans glucoamylase is available (5,26), and a role for this enzyme in sucrose utilization cannot be excluded.…”
Section: Resultsmentioning
confidence: 99%
“…α-amylase and amyloglucosidase enzymes may be used for low-caloric beer production (Dowhanick et al, 1990;Stewart a Sills, 1984).…”
Section: Other Non-saccharomyces Yeastsmentioning
confidence: 99%